Awareness of the Care Team in Electronic Health Records - Vawdrey, D.K.; Wilcox, L.G.; Collins, S.; Feiner, S.; Mamykina, O.; Stein, D.M.; Bakken, S.; Fred, M.R.; Stetson, P.D. (Applied Clinical Informatics, 2011)
Objective: To support collaboration and clinician-targeted decision support, electronic health records (EHRs) must contain accurate information about patients’ care providers. The objective of this study was to evaluate two approaches for care provider identification employed within a commercial EHR at a large academic medical center.Methods: We performed a retrospective review of EHR data for 121 patients in two cardiology wards during a four-week period. System audit logs of chart accesses were analyzed to identify the clinicians who were likely participating in the patients’ hospital care. The audit log data were compared with two functions in the EHR for documenting care team membership: 1) a vendor-supplied module called “Care Providers”, and 2) a custom “Designate Provider” order that was created primarily to improve accuracy of the attending physician of record documentation.Results: For patients with a 3–5 day hospital stay, an average of 30.8 clinicians accessed the electronic chart, including 10.2 nurses, 1.4 attending physicians, 2.3 residents, and 5.4 physician assistants. The Care Providers module identified 2.7 clinicians/patient (1.8 attending physicians and 0.9 nurses). The Designate Provider order identified 2.1 clinicians/patient (1.1 attending physicians, 0.2 resident physicians, and 0.8 physician assistants). Information about other members of patients’ care teams (social workers, dietitians, pharmacists, etc.) was absent.Conclusions: The two methods for specifying care team information failed to identify numerous individuals involved in patients’ care, suggesting that commercial EHRs may not provide adequate tools for care team designation. Improvements to EHR tools could foster greater collaboration among care teams and reduce communication-related risks to patient safety.
Keywords: Provider communication; care team; electronic health records; health information technology; patient care team